Instructional Design Development of Mahilung Mobile Learning Based on the 4-D Model as an Ethno-Edugames Framework for Dayak Cultural Literacy - Maryam Mustika; Eli Karliani; Laila Rahmawati; Widya Karmila Sari Achmad; Karta Jayadi; Firdaus W. Suhaeb; Syahrul (The Indonesian Institute of Science and Technology Research, 2026)
The implementation of cultural literacy in elementary schools still tends to be content-centric and has not been systematically integrated into digital instructional design, particularly in the context of Dayak culture in Central Kalimantan. This study aims to develop a Mahilung Mobile Learning instructional design based on the 4-D model (Define, Design, Develop, Disseminate) as an ethno-edugames framework in strengthening Dayak cultural literacy in elementary school students. The study uses a Research and Development (R&D) approach with a mixed-methods design. The definition stage includes needs analysis, student characteristics, and curriculum review to identify Dayak cultural values ​​relevant to Theme 8